O estudo da geometria por atividades experimentais - REIS, Tárcia Valéria dos Santos (2023)
The objective of this research is to analyze through an exploratory and qualitative study experimental activities in mathematics using geometry. The teaching of geometry can contribute to the formation of the student, in order to favor a particular type of thinking, seeking new situations, being sensitive to their visual impacts and questioning them. Content related to geometry requires concentration and reasoning from the student, in addition to arousing interest in discovery by exploring the content studied and using various pedagogical resources, the teacher will provide this to students. Numerous studies have suggested constructivist learning of 3D geometry, which advocates that students must construct and perceive geometric properties by manipulating 3D objects. In addition, digital learning materials using computer visualization have been advocated to facilitate 3-D geometric learning. The use of concrete materials in the study of Geometry, contrary to what is imagined, provides better learning not only when used with children, but also with any age group. In this way, the present study reached the proposed objective when verifying those experimental activities such as: virtual reality, software, wooden blocks and among others are essential for the teaching of geometry